Why is there so much Inertia in Inflation and Output? A Behavioral Explanation - Yuemei Ji (Center for Economic Studies and ifo Institute (CESifo), 2018)
Serial correlation in macroeconomics is pervasive. Macroeconomic modellers find it impossible to model this feature without relying on serially correlated shocks. Using a behavioral macroeconomic model, I show that serial correlation in inflation and output can easily be explained in the context that agents do not have rational expectation. This important feature is missing in the standard New Keynesian rational expectations models. The rational expectation models need serially correlated exogenous shocks to account for the high serial correlation in inflation and output while the behavioral model produces serial correlation in these variables endogenously. I also show that inertia in the beliefs about the future is a strong force in producing the serial correlation in inflation and output.
Keywords: E00; 330; behavioral macroeconomics; serial correlation; inflation; output gap; inertia in belief; endogenous business cycle